Electron transfer reactions in sub-porphyrin–naphthyldiimide dyads. Issue 30 (19th July 2019) - Küçüköz, Betül; Adinarayana, B.; Osuka, Atsuhiro; Albinsson, Bo
Abstract : A series of donor–acceptor compounds based on a sub-porphyrin (SubP) as an electron donor and naphthyldiimide (NDI) as an acceptor has been designed, synthesized and investigated by time-resolved emission and transient absorption measurements. Abstract : A series of donor–acceptor compounds based on a sub-porphyrin (SubP) as an electron donor and naphthyldiimide (NDI) as an acceptor has been designed, synthesized and investigated by time-resolved emission and transient absorption measurements. The donor and acceptor are separated by a single phenyl spacer substituted by methyl groups in order to systematically vary the electronic coupling. The electron transfer reactions in toluene are found to be quite fast; charge separation is quantitative and occurs within 5–10 ps and charge recombination occurs in 1–10 ns, depending on the substitution pattern. As expected, when steric bulk is introduced on the adjoining phenyl group, electron transfer rates slow down because of smaller electronic coupling. Quantum mechanical modelling of the potential energy for twisting the dihedral angles combined with a simplified model of the electronic coupling semi-quantitatively explains the observed variation of the electron transfer rates. Investigating the temperature variation of the charge separation in 2-methyltetrahydrofuran (2-MTHF) and analyzing using the Marcus model allow experimental estimation of the electronic coupling and reorganization energies. At low temperature, relatively strong phosphorescence is observed from the donor–acceptor compounds with onset at 660 nm signaling that charge recombination occurs, at least partially, through the sub-porphyrin localized triplet excited state. Finally, it is noted that charge separation in allSubP–NDI dyads is efficient even at cryogenic temperatures (85 K) in 2-MTHF glass.